Muhammadiyah dan Islam Wasathyah: Kajian tentang Agency Moderasi beragama melalui Sekolah Muhammadiyah - Munawirur Rahman; Romelah Romelah; Moh. Nurhakim (Journal on Education, 2024)
Muhammadiyah and wasathiyyah Islam are actually two things that cannot be separated because Muhammadiyah is an Islamic organization in Indonesia which has a mission of preaching amar ma'ruf nahi ungkar with an Islamic wasathiyyah approach. This research aims to examine in more depth using a literature approach the role of Muhammadiyah in strengthening religious moderation. The results of this research show that Muhammadiyah is an ideological group that represents Islamic groups in maintaining religious moderation as a national and state commitment. Has Tawassuth's commitment and principles, positions it as a moderate group, maintains balance and is consistent. Muhammadiyah makes Muhammadiyah schools as religious moderation agencies. Religious moderation in Muhammadiyah schools is carried out firstly, the religious da'wah model which is used as a space to implement religious moderation in this section consists of cult activities and religious lectures. Kultum or seven-minute lectures are a means of teaching religious moderation to students. Apart from religious lectures, secondly, Muhammadiyah schools also carry out social and religious activities